2022
DOI: 10.3390/children9111741
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Epilepsy in Children Presenting to Emergency Departments with Their First Afebrile Seizure: A Retrospective Multicenter Study

Abstract: Seizure is one of the most common neurologic disorders in pediatric emergency department visits. Early detection of epilepsy development in children with afebrile seizures is important. We identified predictors of epilepsy development in children with their first afebrile seizure. In this retrospective multicenter study, we enrolled pediatric patients aged 1 month to 18 years who presented with afebrile seizures at the emergency department from January 2017 to December 2020. Multivariable logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Consistent with the findings of Maia et al, 6 we found a 12.7% incidence of first afebrile seizures in patients aged 11-15 years. Furthermore, the recurrence of seizures was significantly higher in patients over 11 years than in those under 5 (RR = 1.316), which is in line with the findings of Woo et al 7 Consistent with previous studies, 8,9 we also found that sex was not associated with recurrence following the first nonfebrile seizure. Studies investigating the risk factors associated with unprovoked seizure recurrence in children have reported recurrence rates of 27-50%, [10][11][12] consistent with our present findings (45.3%).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the findings of Maia et al, 6 we found a 12.7% incidence of first afebrile seizures in patients aged 11-15 years. Furthermore, the recurrence of seizures was significantly higher in patients over 11 years than in those under 5 (RR = 1.316), which is in line with the findings of Woo et al 7 Consistent with previous studies, 8,9 we also found that sex was not associated with recurrence following the first nonfebrile seizure. Studies investigating the risk factors associated with unprovoked seizure recurrence in children have reported recurrence rates of 27-50%, [10][11][12] consistent with our present findings (45.3%).…”
Section: Discussionsupporting
confidence: 93%